(a平方b立方)立方=()?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 05:54:48
(a平方b立方)立方=()?(a平方b立方)立方=()?(a平方b立方)立方=()?原式=a^6b^9
(a平方b立方)立方=()?
(a平方b立方)立方=()?
(a平方b立方)立方=()?
原式=a^6b^9
(a平方b立方)立方=()?
a立方+b立方=?a立方-b立方=?(a+b+c)平方=?
a立方+b立方=(a+b)立方=
已知b平方=ac,求(a立方+b立方+c立方)分之(a平方*b平方*c平方)*(a立方分之1+b立方分之1+c立方分之1)的值
(2a的平方b)的立方/(-4a的平方b的立方)=
已知a的立方+b的立方=27,a平方b-ab平方=-6,求(b立方-a立方)+(a平方b-3ab平方)-2(b立方-ba平方)的值
(-5a的平方b的立方)X( )=15a的立方b的立方
( )/7a的平方b的立方=-7a的立方b的立方+2a的立方
a的立方+b的立方=(a+b)(a的平方—ab+b的平方)
因式分解:a立方+a平方b-ab平方-b立方
【12(a平方b)立方b平方+3a平方(3a平方b立方-ab平方)】➗(3a立方b平方)
(-a)的立方乘(-b的平方)的立方加(-a的立方乘b的平方)是多少
分解因式,一 -2a立方b立方+4a平方b立方-2ab立方.二 9-12(a-b)+4(a-b)平方
-a平方b(a立方b平方-3a平方b+b立方)-2ab平方(a4次方b-3a立方-2ab平方)
已知:a-b=0,求a的立方-(2a的四次方b的立方-a的平方b)-ab的平方-b的立方+2a的立方b的四次方的值.先化简
a平方b平方-c立方b平方-16a立方+16c立方
若a立方+b立方=35,a平方乘以 b-ab平方=-6,a立方-b立方+3ab平方-a平方乘b-2乘 ab平方-b立方的差是多少?
x+y+z=a…x平方+y平方+z平方=b平方…x立方+y立方+z立方=c立方…求xyz